Microeconomic institutions and personnel economics for health care delivery: a formal exploration of what matters to health workers in Rwanda - Pieter Serneels; Tomas Lievens (BMC, 2018)
Abstract Background Most developing countries face important challenges regarding the quality of health care, and there is a growing consensus that health workers play a key role in this process. Our understanding as to what are the key institutional challenges in human resources, and their underlying driving forces, is more limited. A conceptual framework that structures existing insights and provides concrete directions for policymaking is also missing. Methods To gain a bottom-up perspective, we gather qualitative data through semi-structured interviews with different levels of health workers and users of health services in rural and urban Rwanda. We conducted discussions with 48 health workers and 25 users of health services in nine different groups in 2005. We maximized within-group heterogeneity by selecting participants using specific criteria that affect health worker performance and career choice. The discussion were analysed electronically, to identify key themes and insights, and are documented with a descriptive quantitative analysis relating to the associations between quotations. The findings from this research are then revisited 10 years later making use of detailed follow-up studies that have been carried out since then. Results The original discussions identified both key challenges in human resources for health and driving forces of these challenges, as well as possible solutions. Two sets of issues were highlighted: those related to the size and distribution of the workforce and those related to health workers' on-the-job performance. Among the latter, four categories were identified: health workers' poor attitudes towards patients, absenteeism, corruption and embezzlement and lack of medical skills among some categories of health workers. The discussion suggest that four components constitute the deeper causal factors, which are, ranked in order of ease of malleability, incentives, monitoring arrangements, professional and workplace norms and intrinsic motivation. Three institutional innovations are identified that aim at improving performance: performance pay, community health workers and increased attention to training of health workers. Revisiting the findings from this primary research making use of later in-depth studies, the analysis demonstrates their continued relevance and usefulness. We discuss how the different factors affect the quality of care by impacting on health worker performance and labour market choices, making use of insights from economics and development studies on the role of institutions. Conclusion The study results indicate that health care quality to an important degree depends on four institutional factors at the microlevel that strongly impact on health workers' performance and career choice, and which deserve more attention in applied research and policy reform. The analysis also helps to identify ways forwards, which fit well with the Ministry's most recent strategic plan.